Comparison between Galileo CBOC Candidates and BOC(1, 1) in Terms of Detection Performance. (27th March 2008) - Dovis, Fabio; Lo Presti, Letizia; Fantino, Maurizio; Mulassano, Paolo; Godet, Jérémie
Abstract : Many scientific activities within the navigation field have been focused on the analysis of innovative modulations for both GPS L1C and Galileo E1 OS, after the 2004 agreement between United States and European Commission on the development of GPS and Galileo. The joint effort by scientists of both parties has been focused on the multiplexed binary offset carrier (MBOC) which is defined on the basis of its spectrum, and in this sense different time waveforms can be selected as possible modulation candidates. The goal of this paper is to present the detection performance of the composite BOC implementation of an MBOC signal in terms of detection and false alarm probabilities. A comparison among the CBOC and BOC(1, 1) modulations is also presented to show how the CBOC solution, designed to have excellent tracking performance and multipath rejection capabilities, does not limit the acquisition process.